Black Theology in Transatlantic Dialogue - Reddie, A. author. aut Link
XIII, 250 p.
Keywords: In this book, Anthony G. Reddie creates a dynamic conversation between black theologies in the US and in the UK, comparing and highlighting divergences in the respective movements.